2021
DOI: 10.1344/geologicaacta2021.19.9
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Granitoids in Central Sumatra: An Identification of Plate Extension during Triassic

Abstract: Previous investigations of granitoids in Sumatra were focused on age dating with minimum geochemistry composition analysis. The purpose of this study is to define the geochemistry classification of the intrusions in central Sumatra and to explain the rocks' correlation to Southeast Asia tectonic activities. A polarizing microscope was used for petrography description while XRF and ICP-MS were applied for geochemistry measurements. According to the geochemistry, almost all of the intrusions are the I-type volca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(81 reference statements)
0
2
0
3
Order By: Relevance
“…MgO content of ultramafics of list range in 23.31-49%, while SiO 2 between 35.94% and 44.41% (Table 1). Unlike Indonesian S-type granites which are associated with tin, the ultramafics are often correlated with nickel (Irzon, 2019;Irzon et al, 2021). Studies concluded that North Konawe, North Kolaka, and Barru-Bantimala ultramafics are nickel rich, especially in their lateritic horizons (Maulana et al, 2015;Irzon and Abdullah, 2018).…”
Section: Prospecting Mineral Carbonation In Indonesiamentioning
confidence: 99%
“…MgO content of ultramafics of list range in 23.31-49%, while SiO 2 between 35.94% and 44.41% (Table 1). Unlike Indonesian S-type granites which are associated with tin, the ultramafics are often correlated with nickel (Irzon, 2019;Irzon et al, 2021). Studies concluded that North Konawe, North Kolaka, and Barru-Bantimala ultramafics are nickel rich, especially in their lateritic horizons (Maulana et al, 2015;Irzon and Abdullah, 2018).…”
Section: Prospecting Mineral Carbonation In Indonesiamentioning
confidence: 99%
“…Berdasarkan urutan dan sejarah pembentukannya, granitoid di Asia Tenggara dapat diklasifikasikan menjadi empat mandala, yaitu Mandala Timur, Mandala Tengah, Mandala Barat, dan Mandala Gunungapi (Gasparon & Varne, 1995;Cobbing, 2005). Granitoid di Mandala Timur diinisiasi oleh penunjaman Palaeo-Tethys ke bawah Lempeng Indochina-East Malaya, sedangkan Mandala Tengah terbentuk akibat kolisi Sibumasu dengan Indochina-East Malaya (Metcalfe, 2013); (Irzon et al, 2021). Subduksi Ceno-Tethys menyebabkan pembentukan granitoid pada Mandala Barat yang sebagian besar berada di bagian barat Thailand.…”
Section: Pendahuluanunclassified
“…Gambar 1 Pluton Lassi yang berada dalam kisaran Bukit Barisan dan terdiri dari tiga bagian (modifikasi Silitonga dan Kastowo 1995; Irzon et al, 2021).…”
Section: Nama Plutonunclassified
See 1 more Smart Citation
“…Tectonic history of the Southeast Asia region which is composed of continental blocks, namely Sibumasu, Indochina, East Malaya, West Sumatra, West Burma, Simao, and Southwest Borneo is enigmatic (i.e. Barber and Crow, 2009;Metcalfe 2011Metcalfe , 2013Hall and Sevastjanova, 2012;Cottam et al, 2013;Breitfeld et al, 2017;Ng et al, 2017;Hazad et al, 2019;Irzon et al, 2021). Classification of granitic rocks of Southeast Asia into Eastern, Main Range, and Western Provinces is based on continental blocks convergences with several ancient oceans called Palaeo-Tethys, Meso-Tethys, and Ceno-Tethys (Barber, 2000;Barber and Crow, 2003;Metcalfe, 2011Metcalfe, , 2013Jiang et al, 2017;Irzon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%